Ricordando la Shoah. Nota pedagogica - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2014)
This paper develops some considerations on mourning and memory of the Shoah, for the occasion of the Holocaust Memorial Day. It is argued that an educational model for awareness in confronting the collective drama of the Shoah could fully integrate the memory with an analysis of the social processes that still create the development and spread of racism in society, with particular attention to the symbolic meaning evocative of minorities in the processes of social integration.